UPAYA MENINGKATKAN KUALITAS SISWA DALAM MEMAHAMI MATERI SISTEM ORGANISASI KEHIDUPAN MAKHLUK HIDUP MELALUI MODEL TEAM ACCELERATED INSTRUCTION SISWA KELAS 7-E SMPN 1 JEMBER TAHUN PELAJARAN 2014/2015 - Susi Hidayanti (JURNAL PEMBELAJARAN FISIKA, 2020)
Learning problems found that many students lack motivation to learn, less creative and the low frequency of practice exercises and understanding the material. In this study to improve the understanding of the Living Organizational System Organizational System through the Model Accelerated Instruction Model for Class VII students E. The stages of planning and action carried out by the model teacher, the observation stage is carried out by other teachers, and the reflection stage is carried out by the model teacher and other teachers who are observers at the time of implementation for evaluation material in the next cycle. This research was conducted at Jember 1 Public Middle School in class VII-E 2014/2015 academic year. In cycles 1 and 2 the level of completeness of student learning outcomes increases.